Antitumor activity against murine lymphoma L5178Y model of proteins from cacao (Theobroma cacao L.) seeds in relation with in vitro antioxidant activity - Lugo Eugenia; Hernández Rodolfo; Mateos Juan C; Puebla Ana M; Jaramillo María E; Preza Ana M (BMC, 2010)
Abstract Background Recently, proteins and peptides have become an added value to foodstuffs due to new knowledge about its structural analyses as related to antioxidant and anticancer activity. Our goal was to evaluate if protein fractions from cacao seeds show antitumor activity on lymphoma murine L5178Y model. The antioxidant activity of these fractions was also evaluated with the aim of finding a correlation with the antitumor activity. Methods Differential extraction of proteins from unfermented and semi-fermented-dry cacao seeds was performed and characterized by SDS-PAGE and FPLC size-exclusion chromatography. Antitumor activity was evaluated against murine lymphoma L5178Y in BALB/c mice (6 × 104 cells i.p.), with a treatment oral dose of 25 mg/kg/day of each protein fraction, over a period of 15 days. Antioxidant activity was evaluated by the ABTS+ and ORAC-FL assays. Results Albumin, globulin and glutelin fractions from both cacao seed type were obtained by differential solubility extraction. Glutelins were the predominant fraction. In the albumin fraction, polypeptides of 42.3 and 8.5 kDa were found in native conditions, presumably in the form of two peptide chains of 21.5 kDa each one. The globulin fraction presented polypeptides of 86 and 57 kDa in unfermented cacao seed that produced the specific-cacao aroma precursors, and after fermentation the polypeptides were of 45 and 39 kDa. The glutelin fraction presented proteins >200 kDa and globulins components <100 KDa in lesser proportion. Regarding the semifermented-dry cacao seed, it was observed that the albumin fraction showed antitumoral activity, since it caused significant decreases (p < 0.05) in the ascetic fluid volume and packed cell volume, inhibiting cell growth in 59.98 ± 13.6% at 60% of the population; while the greatest antioxidant capacity due to free radical scavenging capacity was showed by the albumin and glutelin fraction in both methods assayed. Conclusion This study is the first report on the biological activity of semifermented-dry cacao protein fractions with their identification, supporting the traditional use of the plant. The albumin fraction showed antitumor and free radical scavenging capacity, however both activities were not correlated. The protein fractions could be considered as source of potential antitumor peptides.